Assessing the contributions of outdoor and indoor sources to air quality in London homes of the SCAMP cohort. (15th August 2022) - Vu, Tuan V.; Stewart, Gregor B.; Kitwiroon, Nutthida; Lim, Shanon; Barratt, Benjamin; Kelly, Frank J.; Thompson, Rhiannon; Smith, Rachel B.; Toledano, Mireille B.; Beevers, Sean D.
Abstract: Given that many people typically spend the majority of their time at home, accurate measurement and modelling of the home environment is critical in estimating their exposure to air pollution. This study investigates the fate and impact on human exposure of outdoor and indoor pollutants in London homes, using a combination of sensor measurements, outdoor air pollution estimated from the CMAQ-urban model and indoor mass balance models. Averaged indoor concentrations of PM2.5, PM10 and NO2 were 14.6, 24.7 and 14.2 μg m −3 while the outdoor concentrations were 14.4, 22.6 and 21.4 μg m −3, respectively. Mean infiltration factors of particles (0.6–0.7) were higher than those of NO2 (0.4). In contrast, higher loss rates were found for NO2 (0.5–0.8 h −1 ) compared to those for particles (0.1–0.3 h −1 ). The average concentrations of PM2.5, PM10 and NO2 in kitchen environments were 22.0, 33.7 and 20.8 μg m −3, with highest hourly concentrations (437, 644 and 136 μg m −3, respectively) during cooking times (6–7 pm). Indoor sources increased the indoor concentrations of particles and NO2 by an average of 26–37% in comparison to the indoor background level without indoor sources. Outdoor and indoor air exchange plays an important role in reducing air pollution indoors by 65–86% for particles and 42–65% for NO2 . Highlights: Mean Indoor/outdoor (I/O) ratios were 1.2 for PM whereas it was 0.84 for NO2 . Higher infiltration factors were found for particles (0.6–0.7) compared to those for NO2 . On average, indoor sources contributed 26–37% of indoor concentrations of particles and NO2 . Outdoor and indoor air exchange plays a critical role in reducing indoor pollutants when indoor sources occur.